Mitigasi dan Adaptasi Struktural Bahaya Banjir Berdasarkan Kearifan lokal Masyarakat Aceh Singkil - Nazli Ismail; Bakhtiar Bakhtiar; Muhammad Yanis; Dian Darisma; Faisal Abdullah (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2020)
Most of the Singkil communities live along the river banks. Their long-term experience has generated some local wisdom in flood hazard mitigation and adaptation. To revitalize the values of the local wisdom, we have researched Cingkam Village, Aceh Singkil District, Aceh Province. A descriptive exploratory method was used in this study. Field data were collected based on field observations, interviews with local communities, and in-depth interviews with community leaders and local government regarding knowledge, experience, implementation, and possibility of developing the local wisdom. The results showed that the Singkil community practice local wisdom on structural mitigation and adaptation in flood hazards. They constructed floating buildings, namely sapao metungkhang, lampung, and bagan, made of logs drifting along the river. The buildings are practically effective, so that daily household and communal activities can still be carried out both in normal conditions and during flooding. However, they tend to disappear due to several factors including shortages of raw materials, progress inland transportation development, relocation of community far from rivers, and dimmed water transportation routes. Although the practices are starting to be abandoned, they still have the potential to be preserved and developed for both flood risk reduction and tourism destinations.